Fragmentation, homogenisation or segmentation? A diary study into the diversity of news consumption in a high-choice media environment. (October 2021) - Slaets, Arno; Verhoest, Pascal; d'Haenens, Leen; Minnen, Joeri; Glorieux, Ignace
A weeklong diary study ( N  = 460) into the exposure to news of Belgian (Flemish) adult media users (aged 25–45) shows that their information consumption is currently relatively diverse. An explanation for the observed diversity is that news consumers in Dutch-speaking Belgium have a wide array of internally balanced news titles and channels at their disposal, which they also actively consult. In addition, the study demonstrates that news consumption patterns span across all media platforms. This study thus illustrates that there is a weak influence of ideological attitudes and psychosocial dispositions on news consumption, measured in time of consumption per media title or channel. These findings call for a revision of theories of selective exposure that disregard the influence that the diversity of information supply can have on the selection procedures of recipients.